Risk factors for acute asthma in tropical America: a case–control study in the City of Esmeraldas, Ecuador. Issue 5 (August 2015) - Ardura‐Garcia, Cristina; Vaca, Maritza; Oviedo, Gisela; Sandoval, Carlos; Workman, Lisa; Schuyler, Alexander J.; Perzanowski, Matthew S.; Platts‐Mills, Thomas A.E.; Cooper, Philip J.
Abstract Background Despite the high asthma rates described in Latin America, asthma risk factors in poor urban settings are not well established. We investigated risk factors for acute asthma among Ecuadorian children. Methods A matched case–control study was carried out in a public hospital serving a coastal city. Children with acute asthma were age‐ and sex‐matched to non‐asthmatics. A questionnaire was administered, and blood, as well as stool, and nasopharyngeal swabs were collected. Results Sixty cases and 119 controls aged 5–15 were evaluated. High proportions of cases were atopic with population‐attributable fractions for atopy of 68.5% for sIgE and 57.2% for SPT. Acute asthma risk increased with greater titers of mite IgE (3.51–50 kU/l vs. <0.70kU/l – OR 4.56, 95% CI 1.48–14.06, p = 0.008; >50kU/l vs. <0.70kU/l – OR 41.98, 95% CI: 8.97–196.39, p < 0.001). Asthma risk was significantly independently associated with bronchiolitis (adj. OR: 38.9, 95% CI 3.26–465), parental educational level (adj. OR 1.26, 95% CI: 1.08–1.46), and presence of sIgE (adj. OR: 36.7, 95% CI: 4.00–337), while a reduced risk was associated with current contact with pets (adj. OR: 0.07, 95% CI: 0.01–0.56). Rhinovirus infection was more frequent in cases (cases 35.6% vs. controls 7.8%, p = 0.002). None of the cases were on maintenance therapy with inhaled corticosteroids and most relied on emergency department for control. Conclusions A high proportion of children presenting to a public hospital with acute asthma were allergic to mite, particularly at high IgE titer. Poor asthma control resulted in overuse of emergency care.